(untitled) (Conference on English Language Teaching, 2023)
In the teaching and learning process, textbooks are defined as the primary fundamentals. Metaphor is used in everyday language as well as in literature. One of metaphorical theories that support this statement is the conceptual metaphor theory. The conceptual metaphor is one of the theories initiated by Goerge Lakoff and Mark Johnson. The aims of this study are to identify the kinds of conceptual metaphor and describe the meaning of metaphorical expression that found in English Textbooks of Senior High School. Furthermore, this research is a qualitative method which is presented in qualitative descriptive. The researcher uses content analysis method in analyzing the data and uses documentation study in collecting the data. The data source was taken from English Textbooks of Senior High School grade 10-12 the data used in this study are words, phrases, and sentences that contain conceptual metaphor. The result of research show that there are 36 conceptual metaphor data that found in English textbooks. The types of conceptual metaphors that often appear are ontological metaphors with 19 data, structural metaphors with 7 data, and orientational metaphors with 10 data. Metaphorical expressions found in the data are in the form of words, phrases and sentences that describe their meaning.